The effect of the cognitive apprenticeship strategy into the achievement and memorization of literature and texts among the fifth literary students - Ghayyib, Natiq Saeed (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed to identify the effect of the cognitive apprenticeship strategy on the achievement and retention of literature and texts among fifth-grade literary students. The researcher used the quasi-experimental method, with partial control. The researcher rewarded the two research groups in grades in the Arabic language subject for the semester. The researcher prepared behavioral goals and teaching plans. Then he prepared an achievement test consisting of (30) statements, including (26) statements of the type of objective tests, and (4) statements of the type of short-answer essay tests. The researcher intentionally chose Ali bin Abi Talib Preparatory School for Boys, and the research sample amounted to (66). students, distributed into two groups, and group (A) consisted of 33 students representing the experimental group. With whom the (cognitive apprenticeship) strategy was used, and Section (B) consisted of 33 students representing the control group with whom the usual method was used. The results of the research revealed the existence of statistically significant differences between the two groups in the post-achievement and retention test. In favor of the experimental group.